(untitled) (Journal of Medical & Health Sciences Review, 2025)
Nuclear fusion is a potential source of clean energy, depending on achieving optimal plasma conditions for sustained reactions. The connection between fusion rate, plasma temperature, and magnetic confinement time is central to evaluating the viability of controlled fusion reactors, especially tokamaks and stellarators.This study aimed to examining the interdependence of fusion reaction rate, plasma temperature, and magnetic confinement time to better grasps the conditions required for obtaining net energy gain. A computational physics-based cross-sectional study was carried out using plasma simulation models and theoretical calculations. A dataset of 10 controlled plasma runs done in a tokamak setting was analyzed. Fusion rates were determined using cross-section formulas for deuterium-tritium (D–T) reactions. Plasma temperatures ranged between 10–25 keV, while magnetic confinement times were measured using diagnostic sensors. Correlation and regression analyses were conducted to assess interaction between the three parameters. Results showed that the fusion rate increased exponentially with rising plasma temperature up to 15 keV, then radiation losses caused the rate to plateau. A significant positive correlation (r = 0.84, p < 0.01) was seen between magnetic confinement time and net fusion yield, emphasizing its important role in maintaining reaction sustainability. The triple product condition (n·T·τ) was validated, confirming that achieving higher plasma temperatures without sufficient confinement is insufficient for net energy gain. Fusion rate is directly effected by plasma temperature and strongly reliant on magnetic confinement time. Meeting the Lawson criteria involves balancing all three components; extended confinement seems to be the most important predictor of sustained fusion. The results highlight the Requirement to maximize confinement approaches in stellarator and tokamak designs so as to generate usable fusion energy.